2014
DOI: 10.1007/s00423-014-1183-9
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic resection in elderly patients: should it be denied?

Abstract: Elderly patients are at higher risk of mortality after pancreatic resection than usually reported case series. Nonetheless, elderly patients can undergo pancreatic resection with acceptable 5-year survival results. Our results contribute for a better, informed decision-making for elderly patients and their family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
0
26
2
5
Order By: Relevance
“…Age and ASA classification did not seem to be associated with hospital costs. This is in contrast with other studies showing that these pre‐operatively identifiable factors are associated with an increased risk for a complication especially with age > 70–75 years or an ASA classification of II or higher . These discrepancies could be attributed to the selection of patients for PD.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Age and ASA classification did not seem to be associated with hospital costs. This is in contrast with other studies showing that these pre‐operatively identifiable factors are associated with an increased risk for a complication especially with age > 70–75 years or an ASA classification of II or higher . These discrepancies could be attributed to the selection of patients for PD.…”
Section: Discussioncontrasting
confidence: 81%
“…This is in contrast with other studies show-ing that these pre-operatively identifiable factors are associated with an increased risk for a complication especially with age > 70-75 years or an ASA classification of II or higher. [33][34][35][36][37] These discrepancies could be attributed to the selection of patients for PD. Only patients in a good pre-operative performance state were accepted for surgery, and they were not excluded only based on age.…”
Section: Hpbmentioning
confidence: 99%
“…Also in the cohort study by Nagrial et al., it was demonstrated that adjuvant chemotherapy in elderly patients was associated with an improved survival to at least a similar degree as for younger patients. Furthermore, it is known that PDs can be safely performed in elderly patients with good postoperative outcomes . Therefore, physicians may be too reluctant in prescribing adjuvant chemotherapy to elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 21 studies were identified (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). A total of 6,933 PDs were collected, and of these, 1,931 PDs (27.9%) were performed in elderly patients.…”
Section: Systematic Reviewmentioning
confidence: 99%